Post-hatching behavior and dispersal of globally vulnerable Moluccan scrubfowl Eulipoa wallacei on Haruku Island, Indonesia - Handy E. P. Leimena; Tati S Syamsudin; Achmad Sjarmidi (Avian Conservation and Ecology)
The Moluccan scrubfowl Eulipoa wallacei has a small global distribution, including on Haruku Island, Indonesia, and is threatened by egg exploitation facilitated by its communal nesting behavior on the coast. The unique features of the Megapodiidae are the absence of parental care after hatching, and the movements of chicks of this species after hatching are not known, even though this must have influenced chick survival. This study examined post-hatching behavior, including distance, dispersal direction, and type of land cover traversed. Nest sites were small patches of sand less than 0.2 ha surrounded by vegetation, while nest holes were individual nests within nest sites. Of the four marked chicks, one died on the eighth day, while the other three survived until the end of the study period. We recorded chick behavior from the surface of the nest hole using a video camera, and four chicks were radio-tracked to monitor their dispersal direction, distance traveled, and habitat use. The hatching time for Moluccan scrubfowl chicks (n = 263) was between 0350–0700 AM. Their behavior was grouped into the resting phase (1.2 ± 0.7 minutes), the phase moving away from the immediate nest hole (0.6 ± 0.2 minutes) by running or flying, and the phase away from the nesting site (5.2 ± 0.5 minutes). After hatching, chicks dispersed 260–350 m in 24 hours, 390–1030 m in weeks 1–4, and 1060–1120 m in weeks 5–6. Habitat used during early hatching is vegetation around the nest site as temporary shelter, and subsequently, dryland forest and mixed dry agricultural habitats as they grow older. This research data supports a conservation approach for Moluccan scrubfowl at the chick stage by maintaining vegetation around nesting sites and the pathways chicks use as they move toward their daily habitat.